ANALISIS PENGARUH JUMLAH PENDUDUK, INDEKS PEMBANGUNAN MASYARAKAT, DAN TINGKAT INFLASI TERHADAP DANA PIHAK KETIGA PT. BPD JAWA TIMUR PERIODE 2004-2013 - Anisah Anisah (Jurnal Ilmiah Ekonomi Bisnis, 2015)
Local governments should be able to improve the welfare of the people by using the economic resources and sources of non-economic optimum. The success of local government in managing, implementing and evaluating the improvement of the welfare of society in every area of the central government judging from some macro indicators ekonomi.Indikator in question is the number of the population, human development index, as well as regional inflation rate in each province. Achievement of regional economic development objectives, policies needed to seek as much as possible in order to use that line with development potential possessed by region.This study used secondary data obtained by Bank Indonesia and the Central Bureau of Statistics. Data processing using multiple linear regression and ANOVA test. The results showed the total population, human development index, and the rate of inflation, affecting the third parties fund of East Java Regional Development Bank. Keywords: DPK, population, inflation, HDI, BPD Java